Marketing Strategies to Attract Millenial Generation Consumers' Buying Intentions - Putu Ayu Titha Paramita Pika (Yayasan Ilomata, 2023)
Purpose of this research is to find out the marketing strategies implemented by MS GLOW attract the buying interest of millennial generation consumers and determine the buying interest of millennial generation consumers towards MS GLOW products. The research uses qualitative methods. The research location was in Semarapura Kelod, Klungkung, Bali, Indonesia. This research sample used purposive sampling with six informants: business owners, employees, and consumers. Researchers used interviews, documentation, observation methods, and data wetness to collect data using triangulation of sources and techniques. Data analysis uses data collection, reduction, display, and Conclusion Drawing. The research results show that the marketing strategy carried out by MS GLOW Klungkung in implementing the marketing mix can be said to be quite successful because one of the main strategies in determining the success of marketing activities on the scale at MS GLOW Klungkung is determining the marketing mix. Implementing marketing strategies to attract consumer buying interest has been carried out effectively by the MS GLOW Klungkung distributor, done offline or online. However, all the marketing strategies that have been carried out to attract millennial consumers, where reviews on social media about MS GLOW products influence trust. The perception of customers with different beliefs about a product means that it is still difficult to attract millennial consumers' buying intention.